Empowering parents in a bedtime storytelling program for children during a pandemic - Ridha Pratama Rusli; Linda Setiawati; Diemas Arya Komara (Universitas Pendidikan Indonesia, 2023)
This article discusses parental empowerment in guiding children during online learning during the COVID-19 pandemic. This program is carried out with a focus on telling stories before going to sleep. The dedication method strengthens parents' understanding that it is essential to tell bedtime stories to increase children's emotional development. The results of the program's implementation show that telling bedtime stories to parents are beneficial for children's development in morals, imagination, interest in reading, and knowledge. This activity also affects the language and emotional intelligence of children. In online learning, the role of parents is essential in accompanying children. This program is carried out as part of KKN at the Universitas Pendidikan Indonesia to overcome the impact of COVID-19 in the education sector. Parents' application of bedtime stories significantly benefits children's development, especially during a pandemic. Parents can apply this method to support children's stories and in subsequent programs to assess the program's effectiveness in the longer term. Abstrak Artikel ini membahas pemberdayaan orangtua dalam membimbing anak selama pembelajaran daring di masa pandemi COVID-19. Program ini dilakukan dengan fokus pada kegiatan berkisah sebelum tidur. Metode pengabdian yang dilakukan adalah penguatan pemahaman kepada orangtua bahwa pentingnya berkisah sebelum tidur untuk peningkatan perkembangan emosi anak. Hasil pelaksanaan program menunjukkan bahwa berkisah sebelum tidur oleh orang tua bermanfaat bagi perkembangan anak dalam moral, imajinasi, minat membaca, dan pengetahuan. Kegiatan ini juga berpengaruh pada bahasa dan kecerdasan emosional anak. Dalam pembelajaran daring, peran orang tua penting dalam mendampingi anak. Program ini dijalankan sebagai bagian atau upaya dari KKN di Universitas Pendidikan Indonesia untuk mengatasi dampak COVID-19 dalam bidang pendidikan. Penerapan berkisah sebelum tidur oleh orang tua memiliki manfaat signifikan bagi perkembangan anak, terutama pada masa pandemi. Disarankan metode ini dapat diterapkan oleh orang tua untuk mendukung perkembangan anak serta pada program selanjutnya dapat mengkaji efektivitas program ini dalam jangka waktu yang lebih panjang. Kata Kunci: Kegiatan berkisah; pandemi COVID-19; pembelajaran daring; pemberdayaan orang tua.